Analysis Application Of Gas-Liquid Mixtures In Low-Pressure Formation Discharge (Eurasian Journal of Engineering and Technology, 2024)
This article provides information on the features of using a gas-liquid mixture to clean the bottomhole of a well, the negative and positive effects of a gas-liquid mixture on the body of a well.